The 2014 Farm Bill and the WTO - Glauber, Joseph W.; Westhoff, Patrick (Wiley, 2015)
The 2014 farm bill reduced expected budgetary costs of US farm programs, according to estimates prepared by the Congressional Budget Office. Cost projections are very sensitive to market conditions and program participation assumptions, and stochastic analysis indicates that farm program costs could easily differ from expected values by $5 billion or more in any given year. By replacing direct payments with new policies that make payments tied to market prices and yields, the bill could have important World Trade Organization (WTO) implications. If the new policies are classified as non‐commodity specific amber box support, projections indicate that existing WTO limits on the current Aggregate Measure of Support would not be exceeded on average, but could be under some market conditions. Furthermore, the new policies are very likely to exceed some WTO rules proposed by various parties in the Doha Round negotiations.